Local capture in Balint's syndrome: effects of grouping and item familiarity. - Shalev, L; Mevorach, C; Humphreys, G (2007)
We assessed the factors contributing to local capture in G.K., a patient with Balint's syndrome. G.K. found it difficult to identify the global shape of a compound stimulus, and his poor identification of the global shape was not resolved by introducing familiar local stimuli that were either from the same category as the global target but not tied to a response (Experiment 1) or that belonged to a different category to the target (Experiment 2). Effects of item familiarity were tested by examining local capture from Hebrew letters on compound English letters. Prior to training with the Hebrew letters, G.K. was able to identify the global compounds (Experiment 3a). In contrast, after training with the letters, there was a significant increase in local capture (Experiment 3b). Two additional experiments examined effects of local grouping. Local capture was reduced when the local elements were rectangles or ellipses and grouped by closure of local elements (Experiment 4). Global discrimination also improved when local items were unfamiliar rectangular figure eights (Experiment 5a). However, these grouping effects were counteracted by effects of familiarity when the local elements were changed slightly to become familiar number eights (Experiment 5b). The data suggest that familiar local items are likely to capture spatial attention, whilst grouping by closure between local elements can help global shapes compete for spatial attention with local elements in such patients. The impairment in global perception in Balint's syndrome is not all-or-none but graded according to the factors influencing local capture.